Symbolic Values of the "Almari Meteng" Tradition in Family Education: A Case Study in East Java, Indonesia - hadiningrum, Lila pangestu (Potret Pemikiran, 2024)
This study examines the contextualization of the interpretative symbolic meaning of the "Almari Meteng" tradition in marriage as family education in Mancon Village, Wilangan District, Nganjuk Regency, East Java. Using qualitative field research methods, including interviews and documentation, the study explores the symbolic values embedded in this tradition and their relevance to family education. The findings reveal that the Almari Meteng tradition, involving the groom bringing household items to the bride's family, carries rich symbolic meanings related to family resilience, gratitude, social values, and strengthening relationships. The tradition reflects important family education values such as harmony, respect, mutual cooperation, spirituality, health awareness, and children's education. The study employs theoretical frameworks including symbolic interactionism, ritual theory, and Bourdieu's concept of habitus to analyze the tradition's social and cultural implications. While facing challenges from modernization and urbanization, the Almari Meteng tradition demonstrates adaptability and continues to play a significant role in preserving cultural identity and instilling important values in family life. This research contributes to understanding the dynamics of local cultural practices in the context of social change and their potential for sustainable cultural preservation.